Strategie finansowe przedsiębiorstwa wobec ryzyka operacyjnego - Łukasik, Gabriela (Financial Strategies in Relation to Operating Risk in Companies, 2006)
Risk in the activity of a company is linked with the risk situations and related decision problems. Operating risk plays a significant role in various risk situations. The company can make choices operating risk through offensive or defensive financial strategies. The article presents the sources of operating risk as well as conditions and consequences of decisions relating to sales revenue, production costs, working assets and sources of their financing. Operating risk is considered though the level of uncertainty and volatility of operating profit and future operating cash flows with particular attention being paid to risk profile characteristic of every company
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 409-419